Trans and Gender-Diverse Latinx Individuals in the Southern United States: Experiences With Violence and Service Utilization - Alvarez-Hernandez, Luis R. (Violence against women, 2025)
Using secondary data from the 2015 U.S. Transgender Survey, we explored transgender and gender-diverse Latinx individuals in the Southern U.S. experiences with transprejudice and antitrans violence at the individual, interpersonal, and structural levels. Findings include high rates of any form of antitrans violence in the past year and intimate partner violence in a lifetime. Most respondents accessed healthcare services in the past year. However, many reported transprejudice and antitrans violence accessing these services. Findings highlight the need for comprehensive changes at all levels to improve the well-being of transgender and gender-diverse Latinx Southerners experiencing gender-based violence.